Interpersonal Group Therapy terhadap Pengetahuan dan Perubahan Sikap Perlindungan Diri dari IMS Pekerja Seks Komersial Jalanan Usia 15-18 Tahun di Denpasar Bali - Levi Tina Sari (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2015)
The province of Bali with the largest number of foreign tourists to the 9.73% growth in 2011, became the public and government concern in the case of HIV/AIDS. Denpasar city was ranked to be the first of people with HIV by 1,949 people (KPA province of Bali, 2012). The study on the sex tourism in ASEAN is reported by the Child Wise Tourism Australia in 2007, Indonesia was considered as the destination for sex tourism which involve children and young women. The aim of the study was to analyze the effect of group therapy self-protection knowledge and attitudes of Commercial street sex workers aged 15-18 years. Method: The design used in this study was pre - experimental design with the design of One Group Pre- test - post-test design. The sample of this study was 18 people consisting of 3 groups, each group consisting of 6 persons. Snowball sampling technique was used to the respondents who met the inclusion criteria. Result: Statistical test results using paired t - test sample showed an increase in knowledge on STI, attitudes of self-protection. Knowledge t = 7243 , the attitude of t = 6,803 with table=2:21. Discussion: The conclusion of this research showed that there were significant effect of the interpersonal group therapy model with knowledge of STI, attitudes of self-protection against STI to the customer. It was suggested that socialization and coaching on the use of condoms should be increased as well as providing sustainable skills in order to become capital for them not to go back into prostitution.